PENGARUH MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR IPA KELAS V SEKOLAH DASAR - Sati, Niken Laras; Sabri, Tahmid; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research used experimental methods with a form of pre-Experimental Design and non-equivalent design.The population of the entire grade V State primary school 56 West Pontianak from two classes totalling 54 students, this research sample was grade V A of 28 students as a class V and class B control as an experimental class of 26 students.Data collection techniques used are measurement techniques and data-collecting instrument is the written test multiple choice-shaped.Based on the analysis of the data on the average results obtained by post-test experiment class 80.04 and average post-test control 74.07.Hypothesis test results using a t-test (Polled Variance) in the get  = 2.993 while for dk (28 26 ? 2 = 52) with significant tarah ? = 5% get  = 1.676, meaning  2.993 > 1.676, then the Ha is received, there are the influence of the use of audiovisual media against the results of student learning on the learning of natural science.Based on the results of the calculation of effect size (ES) in getting ICE = 0.57 which included the criteria of being.Therefore it can be concluded that the use of audiovisual media in learning natural sciences provide positive influence against the learning outcomes of students of class V State primary school 56 West Pontianak. Keywords : The Influence Of Audio Visual, Media, Science Learning, Student Learning Outcomes